Some new codes for isomorphism identification among kinematic chains and their inversions. Issue 1 (1st January 2013) - Dargar, Ashok; Hasan, Ali; Khan, R.A.
The present work deals with problem of identification of isomorphism which is frequently encountered in structural synthesis of kinematic chains. Using the concept of weighed structural matrices some new codes has been proposed to reveal simultaneously link is isomorphic and chain is isomorphic. Firstly, two new codes for each link, called as extended adjacency link value (EALV) and link total loop size (TLS) are developed to detect distinct mechanisms of a kinematic chain. After that for each kinematic chain a new code called as extended adjacency string (EAS) which is a by-product of the same method is developed. The proposed method is easy to compute, reliable and capable of detecting isomorphism in all simple jointed compound kinematic chains. Some examples are also provided to demonstrate the effectiveness of this method.